Society View on Zawā’id Takbir from the Eid Prayer at Darul Istiqamah Islamic Boarding School Makassar - Wanda Nurul Fauzia Wanda; Sabir Maidin; Shawqy Gadallah (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
Zawā’id takbir is a habit that Muslims carry out when carrying out two eid prayers, namely Eid al-Fitr and Eid al-Adha. It becomes the main problem if the views of the people around the Darul Istiqamah Islamic Boarding School Makassar regarding the implementation of the eid prayer without zawā’id takbir. This article aims to reveal the historical aspect of eliminating zawā’id takbir at the Darul Istiqamah Islamic Boarding School Makassar. This type of research is qualitative with a normative-historical approach. The data sources for this research are primary and secondary data. The results showed that the implementation of the eid prayer at the Darul Istiqamah Islamic Boarding School in Makassar still had many similarities with the implementation of the eid prayer in the general public, especially in Indonesia. The difference only lies in the practice of zawā’id takbir, where the Darul Istiqamah Islamic Boarding School Makassar does not practice zawā’id takbir in the eid prayers because the hadith that is the basis for zawā’id takbir is weak. There are still some Muslims who have doubts whether the eid prayer without zawā’id takbir is still valid or not, whether indeed zawā’id takbir was never exemplified by the Prophet. even so, Muslims still show a good attitude, they are not anti to the eid prayer there, never protest or stay away from the pesantren. Even though the four madhhab priests recommend the practice of zawā’id takbir in the eid prayers, none of them oblige it. The law is sunnah not in harmony, so if someone prays eid without zawā’id takbir , the prayer is still valid. So in the case of the Makassar Darul Istiqamah Islamic Boarding School which does not practice takbir zawāeid in the eid prayers, it does not need to be seen as a big problem.